Ways of Tackling Emotional Exhaustion: Attitudes of School Teachers in China - Xinyu, Xie (2022)
Mental health problems and emotional exhaustion have always been major problems faced by employees in industry and business. In recent years, this problem has been exacerbated by economic and technological developments, as well as the recent impact of the epidemic. The teaching profession has been one of the professions most affected by the problem of emotional exhaustion, especially in the Chinese context. In order to alleviate the significant harm that emotional exhaustion causes to teachers, as well as to students and schools, there is a need to find reasonable ways to address the problem. This study uses a quantitative approach, using a questionnaire to collect and analyse data from a sample of Chinese teachers. The main findings are that seven factors (relationship with students, relationship with colleagues, workload, staff voice and fair treatment, organizational support, work-family conflict, and support on family) were negatively and significantly associated with teachers' emotional exhaustion. One of these factors, organisational support, which was influenced by factors such as industry and country, had a positive impact on alleviating teachers' emotional exhaustion, unlike the different results of some of the previous studies. Therefore, individuals and organisations should improve these factors in order to reduce teachers' emotional exhaustion.